2019
DOI: 10.1111/ajt.15255
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant biopsy risk for stable long-term pediatric liver transplant recipients: 451 percutaneous biopsies from two multicenter immunosuppression withdrawal trials

Abstract: Although liver biopsy is the gold standard for assessing allograft health, its attendant risk has deterred its use in routine monitoring of stable liver transplant recipients during long‐term follow‐up. We utilized prospectively collected data on adverse events from 2 clinical trials of immunosuppression withdrawal to quantify the risk of liver biopsy in pediatric liver transplant recipients. The trials included 451 liver biopsies in 179 children. No biopsies led to bleeding requiring transfusion or interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…A previous study using 451 pediatric patients with transplanted liver under stable conditions (i.e., without high doses of corticosteroids) reported no major bleeding complication [ 23 ]. Another previous study identified younger age as a possible risk factor in pediatric patients with native and transplanted liver [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using 451 pediatric patients with transplanted liver under stable conditions (i.e., without high doses of corticosteroids) reported no major bleeding complication [ 23 ]. Another previous study identified younger age as a possible risk factor in pediatric patients with native and transplanted liver [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…38 Liver biopsies suffer from variable interpretation and sampling error, while imaging studies are insensitive. 38,39 Clinical trials are needed to determine predictors of successful immunosuppression withdrawal to allow for personalization of medication regimens.…”
Section: Allograft Healthmentioning
confidence: 99%
“…Chronic allograft injury, both inflammation and/or fibrosis, was reported in a multicenter cohort of stable, long‐term pediatric LT recipients with consistently normal results from liver tests . Complications following protocol liver biopsies performed in post‐pediatric LT recipients were infrequent and resolved quickly, with biopsy‐related cholangitis occurring only in those patients with underlying biliary strictures . Liver biopsies suffer from variable interpretation and sampling error, while imaging studies are insensitive .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compromised immune system of recipients is a risk factor for developing tumors and viral infections that negatively affect the life quality and recipient survival. ( 4 )…”
mentioning
confidence: 99%